RETRACTED: Understanding Entrepreneurship Education Program in Indonesia : Design Thinking - Mulyani, Sri; Ismuni, Mutdi; Mulyadi, Didi (International Journal for Educational and Vocational Studies, 2020)
This paper is retracted by editor due to publication ethics missconducted by authors (Because there are some parties who object to the data presented in the article, where the data has changed and these results can cause multiple interpretations and biases, the authors states that they required for retraction in this article).